Penguatan Konsep Kombinatorika Siswa SMAN 1 Muara Batu Kabupaten Aceh Utara dalam Menghadapi KSN-K Bidang Matematika 2021 - Herizal, Herizal (Jurnal Pengabdian UNDIKMA, 2021)
This community service activity aimed to strengthen students’ understanding of the combinatorics concepts in facing the regency-level of National Science Competition (KSN) in field of mathematics in 2021. The activity was carried out in March-April 2021 for six meetings in the form of training/coaching. The training used both discovery and drilling methods. The location of the activity was at SMAN 1 Muara Batu, North Aceh Regency with four students as the subject who have been selected at the school level and selected to participate in the KSN at the regency level. Data analysis was carried out qualitatively by direct observation to observe the improvement of the students’ comprehension during the learning process. The result obtained was an improvement of the students’ understanding of combinatorics topic. It can be seen in solving problems, the students are able to determine what concepts will be used and able to solve several KSN questions on combinatorics topic.